2016
DOI: 10.1007/s10545-016-9988-z
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor blockade mediated amelioration of mucopolysaccharidosis type I cardiac and craniofacial pathology

Abstract: Mucopolysaccharidosis type I (MPS IH) is a lysosomal storage disease (LSD) caused by inactivating mutations to the alpha-L-iduronidase (IDUA) gene. Treatment focuses on IDUA enzyme replacement and currently employed methods can be non-uniform in their efficacy particularly for the cardiac and craniofacial pathology. Therefore, we undertook efforts to better define the pathological cascade accounting for treatment refractory manifestations and demonstrate a role for the renin angiotensin system (RAS) using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(57 reference statements)
1
8
0
1
Order By: Relevance
“…Nevertheless, we found alteration neither in TGF-β levels nor in its canonical target (SMAD2/3) in heart samples. Per our data, a modest increase in TGF-β expression levels 41,50 with no activation of secondary messenger (p-SMAD2) was found in the aorta of MPS I mice. 50 As ERK, AKT, and TGF-β are related to collagen production, the reduced level of ERK and AKT activities and the unaltered levels of TGF-β, can explain, in part, the absence of collagen deposition on histological specimens.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, we found alteration neither in TGF-β levels nor in its canonical target (SMAD2/3) in heart samples. Per our data, a modest increase in TGF-β expression levels 41,50 with no activation of secondary messenger (p-SMAD2) was found in the aorta of MPS I mice. 50 As ERK, AKT, and TGF-β are related to collagen production, the reduced level of ERK and AKT activities and the unaltered levels of TGF-β, can explain, in part, the absence of collagen deposition on histological specimens.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, given that RAS peptides and its receptors can be produced locally, heart RAS activation may play a more critical role in cardiovascular diseases, contrasting to systemic activation. Indeed, Osborn et al 41 showed a local up‐regulation of angiotensin II receptors type I and II and the activation of angiotensin II conversion enzyme I and II in the aortas of MPS I. Yet, in our study, we did not analyze the angiotensin peptides in the heart; we have analyzed the levels of AT1R, which was unaltered in heart samples.…”
Section: Discussionmentioning
confidence: 74%
“…In particular, they showed data indicating that treatments with an action similar to that of prednisolone may provide relief from at least some of the behavioral aspects of MPS IIIB disease. Osborn et al reported that angiotensin receptor blockade ameliorated MPS I cardiac and craniofacial pathology, suggesting a role for the renin angiotensin system (RAS) in MPS pathology (Osborn et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting perspective comes from mouse model studies, i.e. the potential use of losartan, an angiotensin-1 receptor antagonist, to treat aortopathy in patients with MPS (as in patients with aortopathy related to Marfan syndrome) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%